Remarks on the Tithonian- Berriasian ammonite biostratigraphy of west central Argentina - Riccardi, Alberto Carlos (2015)
Fil: Riccardi, Alberto Carlos. División Paleozoología Invertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina